MENINGKATKAN MOTIVASI SISWA KELAS XII IPA 1 SMA NEGERI 1 SAKTI KABUPATEN PIDIE DALAM PELAJARAN BIOLOGI MENGGUNAKAN MODEL KOOPERATIF LEARNING DENGAN TEKNIK BERNYANYI - Cut Nisna Juwita (Biotik, 2019)
Research entitled "Improving Student Motivation of Class XII Science 1 of SMA Negeri 1 Sakti in Pidie Regency in Biology Lessons Using Cooperative Learning Models with Singing Techniques" The problem formulation is (1) How do students' motivation in using cooperative learning models with singing techniques on principles material human heredity in class XII of SMA Negeri 1 Sakti, (2) How are the activities of students and teachers in using cooperative learning models with singing techniques on the principles of human heredity in class XII of SMA Negeri 1 Sakti, (3) How do students respond to the use of cooperative learning models with singing techniques on the material principles of human heredity in class XII of SMA Negeri 1 Sakti. This research is a classroom action research (CAR), with the subject of the research being students of class XII, collecting data using tests and observation sheets. Data were analyzed using percentage descriptive statistics. The results of data analysis can be concluded that: (1) There was an increase in the learning outcomes of class XII students of SMA Negeri 1 Sakti on the material principles of heredity by using cooperative learning models with singing techniques. This can be seen from the individual completeness of 66 percent in the first cycle to 83 percent in the second cycle. Classical completeness also increased from the first cycle by 50 percent, to 70 percent in the second cycle, (2) Teacher and student activities between the first cycle to the second cycle increased based on the time spent in the second cycle closer to the ideal time than in the first cycle , (3) There is an increase in student motivation on the material principles of human heredity through the use of cooperative learning models with singing techniques. This is seen from the response of students who say that there are benefits gained in learning through the use of cooperative learning models with singing techniques to the material that has been learned.